Hypersensitivity to 35% carbon dioxide in patients with adult separation anxiety disorder - ATH, Ozgur; BAYM, Mehmet; ALKIN, Tunç (Journal of affective disorders, 2012)
Adults with panic disorder (PD) and children with separation anxiety disorder (CSAD) show higher reactivity to CO2. Our hypothesis was patients with adult separation anxiety disorder (ASAD) would show similar hypersensitivity to CO2. In the present study, we determined whether sensitivity to CO2 was enhanced in adult patients with separation anxiety disorder with no history of panic attacks. Patients with PD (n=38), adult separation anxiety disorder (ASAD) patients with no history of panic attacks (n=31), and healthy subjects (n=40) underwent a 35% CO2 inhalation challenge procedure. Baseline and post-inhalation anxiety were assessed with the Acute Panic Inventory, Visual Analog Scale, and Anxiety Sensitivity Index-3 (ASI-3). As hypothesized the rate of CO2-induced panic attacks was significantly greater in PD and ASAD patient groups (55.3% and 51.6% respectively) than healthy comparison group (17.5%). Nine (69.2%) of 13 patients in PD group who have ASAD concurrent with PD had a CO2-induced panic attack. ASI-3 total scores were not different between PD and ASAD groups and both were significantly higher than controls. However, anxiety sensitivity did not predict the occurrence of panic attacks. The researchers were not blind to the diagnosis and there was no placebo arm for comparison. Besides, parameters of respiratory physiology were not evaluated. ASAD was associated with CO2 hypersensitivity quite similar to PD. This finding partly unfolds the complex relationship of ‘CSAD, PD, and CO2 hypersensitivity’ and indicates that CO2 hypersensitivity and separation anxiety extend together beyond childhood.